(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
When you are in a class of 30 students, do you think that the teacher could give the same attention to all or you could get the proper education you need? It is a tough-provoking question. Homeschooling is a method of educating school-aged children at home or in another setting besides schools. Families use less formal and more individualized learning methods that are not the same as in public schools. Homeschooling is managed by a parent, tutor, or online teacher. According to recent data, homeschool enrollment has grown by 2% to 8% annually, but its growth surged in 2020-2021. During the pandemic, homeschooling has proven to be the safest alternative education, around 300 million students have been homeschooled all over the world. Since homeschooling has become a worldwide phenomenon, Uzbekistan should also accept the approval of the homeschooling system. Although there may be some uncertainty regarding homeschooling, this is due to several reasons: flexibility, better academic achievements, family ties, prevention of bullying, and so on.